Burning Behavior and Parameter Analysis of Biodiesel Pool Fires. Issue 2 (1st February 2018) - Sun, Hao; Wang, Changjian; Liu, Haoran; Li, Manhou; Zhang, Aifeng; Xu, Mingjun
ABSTRACT: The experiments were systematically performed on the burning behavior and parameter analysis of biodiesel pool fires. The circular and square pools were used for axisymmetric source. The effects of pool material, pool size, and fuel thickness on fire evolution were discussed in detail. The typical fire parameters such as burning rate, mean flame height, as well as plume axial temperature, were measured to explore the biodiesel combustion properties. The results indicate that the biodiesel combustion process follows three stages as most ordinary fuels, i.e., initial growth, quasi-steady burning, and decay to extinction. With an increase in pool size or fuel thickness, the burning rate increases gradually. The mean flame height increases along with linearly. A non-dimensional number is proportional to the value of with a 1/10 power. and for biodiesel pool fires were derived to be 0.012 kgm –2 s –1 and 8.1, based on a modified exponential expression of burning rate. Three correlations were developed to predict burning rate, mean flame height, and plume axial temperature by fitting the experimental data.